Effectiveness of Implementing Hazardous and Toxic Waste (B3) Management Standards in Improving Knowledge, Attitudes, and Compliance in Hazardous Waste - Agus Riyadi; Kusbaryanto Kusbaryanto (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2026)
Background: Hazardous and toxic waste (B3) generated by hospitals poses significant risks to healthcare workers, patients, and the environment if not properly managed. Despite the implementation of waste management systems and training programs, staff compliance with standard operating procedures (SOPs) often remains suboptimal. This study aimed to evaluate the effectiveness of implementing hazardous and toxic waste management standards in improving knowledge, attitudes, and compliance among hospital staff. Method: A mixed-methods approach with a quasi-experimental pretest–posttest control group design was employed. A total of 120 respondents were divided into intervention and control groups. Quantitative data were analyzed using paired t-tests and Wilcoxon tests, while qualitative data were analyzed thematically. Result: The results showed significant improvements in the intervention group, with increases in knowledge and attitudes (p < 0.0001) and compliance (p = 0.001). However, the magnitude of change in compliance was smaller compared to knowledge and attitudes. Qualitative findings indicated that while training improved awareness and understanding, sustained compliance was strongly influenced by organizational factors, including monitoring, supervision, and institutional support. Conclusion: In conclusion, training-based implementation of hazardous waste management standards is effective in improving knowledge and attitudes but insufficient to ensure consistent compliance. Strengthening organizational support through continuous monitoring and supervision is essential to promote sustainable behavioral change in healthcare settings.